FORMULASI TEPUNG KOMPOSITTERHADAPMIE BASAH MENGGUNAKAN RESPONSE SURFACE METHODOLOGY - Mita Ramadiyanti; Yusep Ikhrawan (Paspalum: Jurnal Ilmiah Pertanian, 2016)
Sweet potato and jackfruit seeds are local resources that can grow well in tropical climate of Indonesia that has a high level of productivity. Thus, food diversification program through the use of local resources is expected to address people's reliance on products of flour-based noodles. This study is divided into three main stages, namely formula optimization, analysis, and organoleptic. Optimization stage formula begins by determining the maximum and minimum points substitution of each flour. For jackfruit seed flour, sweet potato flour and wheat flour made wet noodle-making with the level of substitution of 10% to 80%. Analysis of the product consists of a physical analysis ie water absorption in the range of 8.5% to 9.5%. Chemical analysis of water content with the result of 0.83% to 0.97%, Abu 0.0087 to 0.0094 levels, protein content of 8.5% to 9.5%, fat content of 0.0075 to 0.0084, starch 27.74 until 27.78, crude fiber 0.02 to 0.07, and a yield of 1 to 1.7. The solution formula with the most optimal response,ie wet noodle formula with 33.33% jackfruit seed flour, sweet potato flour 33.33%, 33.33% wheat flour